Determinants of Partnership in Micro and Small-scale Manufacturing Firm - Janaska Nurrachmat (Universitas Negeri Malang, 2025)
This study aims to analyze the determinants of micro and small firms to conduct a partnership with other institutions. Using logit and probit this research estimates which factors that increase or decrease the probability of forming a partnership among micro and small firms. This study uses the data from Indonesian Statistics Bureau to obtain detailed aspects from each micro and small business, this study also attempts to link the characteristics of larger firm within the same industry group that might have influence on forming a partnership among smaller firms. The result of this study shows that factors which have strong connection with business formality increase the probability of forming a partnership with other institutions